(untitled) (ENTHYMEMA, 2017)
This paper aims to highlight some interesting convergences between the theory of the meaning-construction of the literary text proposed by Iser in The Act of Reading and Pierre Hadot’s work on the hermeneutics of the text in ancient philosophy. As we know, Hadot interprets the specificities of the ancient philosophical text as functional to guide the mind of the reader in a path that does not only have a cognitive purpose, but rather a spiritual one. The concept of «spiritual excercise», central to Hadot’s work, presents similarities – that are potentially very productive – to the model of the use of the literary text in Iser. Moreover, it is apt to show the extraordinary theoretical importance of a series of details, which are seemingly quite technical. In particular, a dialogue between the two approaches of Iser and Hadot allows posing in a new way a question that literary theory typically marginalizes: that of the pragmatics of the literary text.